Pengembangan Label Desain Kemasan Susu Kefir Guna Peningkatan Brand Awareness Wow Suke - Haris Setyawan; Zainudin, Ahmad; Jogatama Purhita, Edy (UNIVERSITAS STEKOM, 2025)
This study aims to measure the effectiveness of packaging label design and promotional media (brochures) in increasing brand awareness of the WOW SUKE kefir milk and ice cream products. The method used is a Brand Lift Study, conducted through surveys with 53 respondents before and after exposure to the promotional materials. The results show a significant increase in brand awareness, from 21.1% before exposure to 49.1% after, indicating a growth of 132.7%. The brand recall rate reached 98.1%, meaning the majority of respondents immediately recalled the WOW SUKE brand when thinking of kefir milk. However, brand recognition was only 49.1%, with 50.9% of respondents still unfamiliar with or uncertain about the brand's existence. Visual design elements—such as colors, imagery, and information layout—were rated very positively by most respondents, suggesting that clear and attractive visual communication can effectively enhance brand perception. In conclusion, the study demonstrates that well-crafted packaging and promotional materials significantly improve brand awareness. Nevertheless, further improvements in communication strategy and promotional distribution, particularly through digital channels, are necessary to broaden audience reach and strengthen brand recognition.